2005
DOI: 10.1111/j.1365-201x.2005.01486.x
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory muscle performance with stretch‐shortening cycle manoeuvres: maximal inspiratory pressure–flow curves

Abstract: The maximal inspiratory pressure-flow capacity can be enhanced with SSC manoeuvres in a manner analogous to increases in the force-velocity relationship with SSC reported for skeletal muscles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…This principle, first defined in limb muscles, was later demonstrated for human inspiratory muscles by Topulos, et al (436) who showed that healthy volunteers develop higher mouth pressures during maximum plyometric maneuvers than during maximum static efforts against an occluded airway. More recently, Tzelepis and associates (444) reported that plyometric contractions performed immediately before an inspiratory effort can augment maximum inspiratory power, mimicking limb muscle performance in a stretch-shortening cycle (50). …”
Section: Force-length Relationshipmentioning
confidence: 99%
“…This principle, first defined in limb muscles, was later demonstrated for human inspiratory muscles by Topulos, et al (436) who showed that healthy volunteers develop higher mouth pressures during maximum plyometric maneuvers than during maximum static efforts against an occluded airway. More recently, Tzelepis and associates (444) reported that plyometric contractions performed immediately before an inspiratory effort can augment maximum inspiratory power, mimicking limb muscle performance in a stretch-shortening cycle (50). …”
Section: Force-length Relationshipmentioning
confidence: 99%
“…The stretch-shortening cycle is a well-accepted property of the muscular function by which the skeletal muscles can increase their power output [Bosco and Komi 1979,Cronin, et al 2001,Komi 2000,Takarada, et al 1997,Walshe, et al 1998] and is another potential mechanism that can explain the greater work of breathing. The respiratory muscles can similarly increase their power output with manoeuvers in which respiratory muscle contraction is immediately preceded by an eccentric contraction of the respiratory muscles [Tzelepis, et al 2005]. In our study, the high IPAP increased end-inspiratory chest wall volume when our participants breathed through the VitaBreath device.…”
Section: Discussionmentioning
confidence: 46%
“…9,27 With pauses of about 4-6 s at TLC, the decreases in PEF may range from 6 to 13% in the healthy volunteers. 5,7,23 The decrement in PEF appears to be greater when the preceding inspiration is slow. In certain patients, particularly COPD or cystic fibrosis, the difference in PEF and other spirometric parameters can be much greater, probably reflecting the time-constant inequalities within the lungs.…”
Section: Article In Pressmentioning
confidence: 93%
“…The transition from an eccentric to a concentric contraction can augment respiratory muscle force output in a manner similar to that described in peripheral muscles. 6,[22][23][24][25] In contrast, a breath-hold at TLC neutralizes the effect of fast inspiration on the effective elastic recoil pressure; it allows stress relaxation in both the airway wall and lung parenchyma to occur and thus increases the airway compliance and decreases the effective lung elastic recoil pressure. 5,8,26 Long post-inspiratory pauses at TLC may also offset the augmentation of expiratory muscle force related to stretchshorten cycle.…”
Section: Article In Pressmentioning
confidence: 99%